A new species of the genus Notodoma Lacordaire, 1854 (Coleoptera, Histeridae, Exosternini) from Korea, with a revised key to species of the genus - Seung, Jinbae; Lee, Seunghyun; Lee, Minhyeuk; Lee, Seunghwan (Zootaxa, 2024)
A new species of the genus Notodoma Lacordaire, 1854 (Coleoptera, Histeridae, Exosternini), Notodoma koreanum sp. nov., is described from Korea. Most of them recognized from various fungi colonies, feeding on small insect eggs or larvae, as well as fungi. We present the descriptions and images of diagnostic characters for Korean Notodoma species, including Notodoma fungorum Lewis, 1884. Additionally, a revised key to all seven species of the genus Notodoma worldwide, including the newly described species, is provided.